2024
DOI: 10.1039/d3sm01199b
|View full text |Cite
|
Sign up to set email alerts
|

Geometric learning of knot topology

Joseph Lahoud Sleiman,
Filippo Conforto,
Yair Augusto Gutierrez Fosado
et al.

Abstract: Knots are deeply entangled with every branch of science. One of the biggest open challenges in knot theory is to formalise a knot invariant that can unambiguously and efficiently distinguish...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Other open knot classification schemes exist but do not satisfy all requirements. Sleiman et al [26] showed a neural network trained on writhe representations of knots can track a knot's topology as it unties, but it cannot be identified with known invariants and lacks smooth interpolation.…”
Section: • For Closed Chains It Should Reproduce Values Of Establishe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other open knot classification schemes exist but do not satisfy all requirements. Sleiman et al [26] showed a neural network trained on writhe representations of knots can track a knot's topology as it unties, but it cannot be identified with known invariants and lacks smooth interpolation.…”
Section: • For Closed Chains It Should Reproduce Values Of Establishe...mentioning
confidence: 99%
“…We simulate polymer knots using a model used to simulate topologically complex polymers in previous works [13,26]. We use a parameterization that models DNA at the low ionic strengths used in fluorescence experiments, in which the persistence length is ten times the effective width of the molecule [38], and the contour length is ten to twenty persistence lengths.…”
Section: Langevin Dynamics Simulationmentioning
confidence: 99%
“…From the other perspective, deep learning models have demonstrated exceptional abilities in recognizing and classifying patterns. By training these models on extensive data sets containing random curve , and protein-like chains with known knot types, it becomes feasible to create reliable algorithms for automating the identification and classification of knots within these intricate structures. Braghetto et al and Sleiman et al demonstrate the effectiveness of long short-term memory (LSTM) based on neural network (NN) in accurately discerning knot types in highly geometrically complex entangled structures. Moreover, Sleiman et al have in fact shown indirectly that these methods can work for open curves since their approach is able to locate the knotted portion.…”
Section: Introductionmentioning
confidence: 99%
“…Braghetto et al and Sleiman et al demonstrate the effectiveness of long short-term memory (LSTM) based on neural network (NN) in accurately discerning knot types in highly geometrically complex entangled structures. Moreover, Sleiman et al have in fact shown indirectly that these methods can work for open curves since their approach is able to locate the knotted portion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation